Gross total resection rates of grade II/III intramedullary ependymomas using the surgical strategy of en-bloc resection without intra-operative neurophysiological monitoring. (4th May 2017) - Sweeney, Kieron J.; Reynolds, Matt; Farrell, Michael; Bolger, Ciaran
Abstract: Introduction: Grade II and III intramedullary ependymomas [IME] are circumscribed with a plane of cleavage that should facilitate high gross total resection rates (GTR). Gross total resection of grade II/III IME is superior to subtotal resection (STR) and radiotherapy (RTx) for progression-free and overall survival. We sought to compare our GTR with other series that have utilised standard intraoperative monitoring techniques and we explored factors that may influence rates of resection. Materials and methods: Database search and retrospective chart and radiological review of all grade II or III spinal ependymomas over a 10-year period from the senior authors practice. Comprehensive PubMed search to identify similar series that identified histology, McCormick Function scores (MCC) preoperatively and post-operatively, surgical strategy and use of intraoperative monitoring. Standard statistical analysis was performed. Results: Seventeen patients were identified: 16 grade II and one grade 3. GTR was 94.12%. Factors that correlated with a decline in MCC were longitudinal extension of the tumour ( p  = 0.0238) and presentation with motor signs and symptoms ( p  = 0.0223). There was no statistical difference between preoperative factors that influence post-operative outcomes in the current study when compared with other published series. There was no statistical difference between preoperative and postoperative MCC scores between our series and other published series. Discussion: The current series with a GTR of 94.12% compares favourably with other published series with GTRs of 55.8–84% with no significant difference in functional outcomes. Series with low GTRs should examine their operative strategy or false-positive alarm rates which may lead to higher STRs. This series should be viewed as a unique opportunity to benchmark GTRs of circumscribed intramedullary tumours.